Young adults' coping strategies against loneliness during the COVID-19-related quarantine in Greece. (17th April 2021) - Golemis, Adrianos; Voitsidis, Panteleimon; Parlapani, Eleni; Nikopoulou, Vasiliki A; Tsipropoulou, Virginia; Karamouzi, Panayiota; Giazkoulidou, Aikaterini; Dimitriadou, Aikaterini; Kafetzopoulou, Christina; Holeva, Vasiliki; Diakogiannis, Ioannis
Summary: COVID-19 and the related quarantine disrupted young adults' academic and professional life, daily routine and socio-emotional well-being. This cross-sectional study focused on the emotional and behavioural responses of a young adult population during the COVID-19-related quarantine in April 2020, in Greece. The study was conducted through an online survey. A total of 1559 young adults, aged 18−30 years, completed Steele's Social Responsibility Motivation Scale and the De Jong Gierveld Loneliness Scale, and answered questions about compliance with instructions, quarantine-related behaviours and coping strategies. According to the results, participants displayed a relatively high sense of social responsibility ( M = 16.09, SD = 2.13) and a trend towards moderate feeling of loneliness ( M = 2.65, SD = 1.62); young women reported significantly higher levels of loneliness than men. The majority complied with instructions often (46.4%) or always (44.8%). Significantly more women created a new social media account and used the social media longer than 5 h/day, compared with men. Resorting to religion, practicing sports and sharing thoughts and feelings about COVID-19 with others predicted higher levels of social responsibility; humour, practicing sports and sharing thoughts and feelings about COVID-19 with others predicted lower levels of loneliness. Conclusively, COVID-19 is expected to have a significant psychological impact on young adults. Currently, Greece is going through the second quarantine period. This study raises awareness about loneliness in young adults during the COVID-19-related quarantine and highlights the importance of developing online programmes, attractive to younger people, to nurture adaptive coping strategies against loneliness. Lay Summary: Young adulthood is a critical developmental period, related with significant changes in life roles. COVID-19 disrupted young adults' academic and professional life, daily routine and socio-emotional well-being. This cross-sectional study investigated social responsibility, compliance with health guidelines, loneliness, coping strategies and quarantine-related behaviours in a sample of 1559 young adults, aged 18−30 years, during the first COVID-19-related quarantine in April 2020, in Greece. According to the results, participants displayed a relatively high sense of social responsibility and complied often/always with guidelines. A trend towards moderate feeling of loneliness was observed; young women reported significantly higher levels of loneliness than men. Significantly more women created a new social media account, and used the social media for longer hours, compared with men. Humour, practicing sports and sharing thoughts and feelings about COVID-19 with others predicted lower levels of loneliness. Currently, Greece is going through the second COVID-19-related quarantine, which has no foreseeable end. This study raises awareness about loneliness in young adults, a negative emotional state that should not be overlooked during this novel public health crisis. The COVID-19 pandemic offers the opportunity to develop online programmes nurturing adaptive coping strategies to reduce loneliness in young adults.